Real-Time Adaptive Scalable Texture Compression for the Web - Oom, Daniel (My University, 2016)
This thesis investigates using Adaptive Scalable Texture Compression in real-time to improve memory utilization in web browsers. A fast encoding method that uses heuristics and avoids the commonly used branch and bound method is presented. Performance benchmarks and quality comparisons against other commonly used encoders show that it is possible to compress textures with reasonable quality in real-time.
Keywords: Data- och informationsvetenskap; Computer and Information Science